THE CHILD AS A PROTAGONIST IN EARLY CHILDHOOD EDUCATION: FROM NURSERY TO KINDERGARTEN (International Seven Journal of Multidisciplinary, 2025)
This article addresses the theme of children as protagonists in Early Childhood Education, focusing on the period from nursery to kindergarten. The research is based on the contemporary conception of childhood, which recognizes children as subjects with rights, active in the construction of knowledge, and effective participants in social and educational interactions. The main objective is to reflect on pedagogical practices that value listening, autonomy, and child participation in the learning process. The methodology adopted is qualitative in nature, based on bibliographic research, through the analysis of academic works, official documents, and recent studies addressing child protagonism, the organization of educational spaces, and teacher performance. The results indicate that, to ensure children's protagonism from the earliest years of life, it is necessary to invest in pedagogical practices that respect individual time and rhythms, promote environments rich in stimulation, and ensure children's effective participation in daily school decisions. It was also observed that the role of the educator must be reconsidered, adopting a mediating, sensitive, and observant stance, capable of interpreting the multiple forms of children's expression. Furthermore, strengthening the partnership between school and family appears essential for the child's comprehensive development and for building an educational environment consistent with children's experiences. It is concluded that promoting child empowerment requires institutional commitment, ongoing training for education professionals, and intentional pedagogical planning guided by values of respect, listening, and valuing children's experiences. When recognized as active subjects in their developmental process, children develop cognitive, affective, and social skills that enable them to participate critically, creatively, and responsibly in different life contexts.